Identification of the Type of Strategic Policy for Sustainable Development on the Basis of Territorial Characterization. A Case Study in Canton Baños de Agua Santa, Tungurahua, Ecuador - Vasconez, Jose Fabian Fonseca; Casco, Andrea del Pilar Ramirez; Diaz, Mario Alfonso Arellano; Guale, Xavier Sulca (Scientific Research, 2017)
This study was carried out in Baños de Agua Santa, Province of Tungurahua-Ecuador; From the time of Spanish colonization to the present day, the failure to implement sustainable development policies has led to the decline of some economic activities and has driven tourism as the main source of income without structured sustainable guidelines with established planning for which becomes a fundamental alternative axis, generating the depletion of tourism resources and territorial disorder, the product of an imposing mercantilist system that guides competitiveness in an indiscriminate way. In correspondence the objective was to identify the type of strategic policy for the sustained development of the tourist destination referred to. Methodologically the study uses theoretical methods such as analysis and synthesis, inductive-deductive, historical-logical, others of the empirical level, among which we can cite the criterion of experts, matrices of analysis such as: external factor evaluation (EFE), evaluation of Internal factors (EFI), SWOT analysis, strategic evaluation and position of action (PEEA) and descriptive statistics. The results obtained were the determination of the present and future incidence of economic activities in the territory under study and the projection of the type of strategic policy for sustainable and responsible management of natural, cultural, socio-productive resources, preventing different Economic cycles, through the evaluation of their productive factors.
Keywords: Processes Management; Sustainability; Territorial Ordering; Tourist Destination